Closed Loop Vector Control of the Modular Multilevel Matrix Converter for Equal Input-Output Operating Frequencies - Rojas-Lobos, F; Diaz-Diaz, M (Institute of Electrical and Electronics Engineers Inc., 2018)
The Modular Multilevel Matrix Converter (M3 C) is an AC-to-AC Modular Multilevel Converter composed of H-Bridge Power Cells connected to flying capacitors. This converter has been proposed as a solution to high-power drive applications due to its characteristics such as high power quality, medium or high voltage operation and control flexibility. However, the energy balancing of this converter is complex when the Input Port has a frequency close to the Output Port frequency because large voltage fluctuations can appear in the flying capacitors. Consequently, this paper proposes a novel Closed-Loop Vector Control Strategy, which is implemented in dq synchronous frames, to allow the operation of the converter in a broad range of operating frequencies. Extensive discussion of the model and control of the M3C is presented. The effectiveness of the proposed Control Strategy is validated through simulations and experimental results obtained with a 27 power-cells prototype. © 2017 IEEE.